UCDP External Support Data - UCDP External Support - Disaggregated/Supporter Dataset - Högbladh, Stina; Pettersson, Therése; Themnér, Lotta (Uppsala University, 2015)
The UCDP, Uppsala Conflict Data Program, contains information on a large number data on organised violence, armed violence, and peacemaking. There is information from 1946 up to today, and the datasets are updated continuously. The data can be downloaded for free, and available in several different versions.

The UCDP External Support Data contains information of external support in intrastate conflicts, 1975-2010. Provides information of kind of support, extern actor and specific year. The data is divided into two separate datasets which are analogous, i.e. contain identical data structured in a different manner to simplify various types of research such as different types of statistical analyses.

Purpose:

The Uppsala Conflict Data Program (UCDP) collects information on a large number of aspects of armed violence since 1946.

The dataset provide data where the unit of analysis is a warring party-year, providing information on the existence, type, and provider of external support for all warring parties (actors) coded as active in UCDP data, on an annual basis.The dataset contains information for the time-period 1975–2010.

UCDP, Uppsala Conflict Data Program vid Uppsala universitet, innehåller stora mängder data över organiserat våld, väpnade konflikter och fredsarbete. Idag täcker UCDP´s data över hela världen, från 1946 och framåt, och finns presenterade i 13 olika dataset som kontinuerligt uppdateras. Datan finns tillgänglig för gratis nedladdning och användning via UCDP´s hemsida.

UCDP External Support Data innehåller information om externt stöd i inomstatliga konflikter, mellan åren 1975-2010. Datan beskriver vad för typ av stöd, från vilken aktör och vilka specifika år det gavs. Datan finns i två olika dataset som är identiska avseende innehåll men har strukturerats på olika sätt.

Syfte:

Syftet för UCDP är att samla olika typer av information om väpnade konflikter från hela världen, från 1946 fram till idag.

Ett dataset som ger data över externt stöd i inomstatliga konflikter, baserat på stridande part-år. Information om förekomst och typ av stöd samt vem/vilka som ger stödet. Täcker tidsperioden 1975-2010.
UCDP External Support Data - UCDP External Support - Primary Warring Party Dataset
Keywords: internal political conflict; inrikespolitiska konflikter; conflict; konflikt; armed forces; väpnade styrkor; Conflict, security and peace; Konflikter, säkerhet och fred; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap